Analiza SWOT produktu turystycznego regionu na przykładzie euroregionu Nysa - Zawadzki, Piotr (Tourist Product SWOT Analysis of a Region Based on the Example of Nysa Euroregion, 2005)
The article presents opportunities for using SWOT analysis as the evaluation method for the current market situation analysis. Economic development of a given region requires competitive conditions to be created, as compared to other areas. Due to the complexity of this process adequate analyses should be carried out, which allow for evaluating the region' s tourist potential. The application of SWOT analysis for the region allows for collecting and presenting information in an orderly manner, on the basis of which the given area development variants can be worked out. The application of strengths allows for emphasizing the given region' s advantages, while introducing order into weaknesses underlines the scale of the occurring problems. In the hereby article the author presents SWOT analysis based on an example of the specific region, namely the Nysa Euroregion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 56-68